Analisis Tingkat Pengetahuan Pasien Hipertensi Terhadap Kepatuhan Kontrol Dirumah Sakit Umum Kota Tarakan - Murliana, Murliana; Sulidah, Sulidah; Damayanti, Ana; Darni, Darni (Universitas Malahayati, 2024)
ABSTRACT Hypertension is often referred to as the silent killerbecause the symptoms are not visible and are only seen when the problems arise. The higher the blood pressure, the greater the risk of complications accuring. The complication can occur, if it is not detected early nor treated adequately. Compliance with treatment and routinecontrol can minimize the risk of complications. This research aimed to determine the relationship between the knowledgelevef of hypertension patients and compliance control. This research was quantitative using a quasi-expeimental design with a pretest-posttest control group design. The number of sample was 36 respondents chosen by using systematicsampling technique where 18 respondents as the intervention groupand the 18 respondents as the control group. The data on patientsknowledge were obtained using a questionnaire and the control compliance using observation sheet. The result showed that intervention group obtained p=0.005 which indicated that there was a relationship between the knowledge level and control compliance of hypertension patients, where as control group obtained p=0.549 which meant that there was no relationship between the knowledge level and control compliance of hypertension patients. The level of knowledge was mostly good.the level of contrl compliance of hypertension patients from both the intervention group and the control group was mostly compliant. The conclusion from this research was that in the intervention group, there was a relationship between the knowledge level and control compliance of hypertension patient, while in the control group, there was no relationship between the knowledge level and control compliance of hypertension patientsat General Hospital of Tarakan City. Keywords: Control Compliance, Hypertension, Knowledge ABSTRAK Hipertensi sering disebut sebagai silent killer karena gejalanya tidak terlihat dan baru terlihat saat masalah muncul. Semakin tinggi tekanan darah semakin besar risiko terjadi komplikasi, komplikasi dapat terjadi bila tidak dideteksi secara dini dan mendapatkan pengobatan yang memadai. Kepatuhan pengobatan dan kontrol secara rutin dapat meminimalisirkan risiko komplikasi. Penelitian ini bertujuan untuk mengetahui hubungan tingkat pengetahuan pasien hipertensi terhadap kepatuhan kontrol. Jenis penelitian ini adalah kuantitatif dengan menggunakan desain quasy experiment pre test-post test control group desain. Jumlah sampel 36 responden,18 responden kelompok intervensi dan 18 responden kelompok kontrol dengan teknik sampling sistematis. Pengambilan data pengetahuan dengan menggunakan kuesioner dan lembar observasi untuk kepatuhan kontrol. Hasil pada kelompok intervensi diperoleh hasil p=0.005, artinya ada hubungan tingkat pengetahuan terhadap kepatuhan kontrol pasien hipertensi. Sedangkan pada kelompok kontrol diperoleh nilai p=0.549, artinya tidak ada hubungan antara tingkat pengetahuan terhadap kepatuhan kontrol pasien hipertensi. Pengukuran tingkat pengetahuan sebagian besar adalah baik. Tingkat kepatuhan pasien hipertensi dari kelompok intervensi maupun kelompok kontrol sebagian besar adalah patuh. Kesimpulan dari penelitian pada kelompok intervensi, ada hubungan tingkat pengetahuan terhadap kepatuhan kontrol pasien hipertensi pada kelompok kontrol tidak ada hubungan antara tingkat pengetahuan terhadap kepatuhan kontrol pasien hipertensi di Rumah Sakit Umum Kota Tarakan. Kata Kunci: Hipertensi, Kepatuhan Kontrol, Pengetahuan